ANALISIS KESADARAN KEAMANAN PANGAN PADA MASYARAKAT DESA SESAOT: STUDI KASUS MELALUI SOSIALISASI INTERAKTIF - Sevina Kundiah Saputri; P.M, Awanda Oktri; Ekasari, Yunita; Yasa, I Wayan Sweca (Universitas Mataram, 2025)
Food safety is a crucial aspect of maintaining public health and well-being. The community of Sesaot Village, West Lombok, which relies heavily on agricultural products and local food processing, needs a strong understanding of food safety practices. This study aims to enhance public awareness of food safety through socialization and evaluation using pre-test and post-test questionnaires. The methods included interactive presentations on food safety and assessments to measure participants' knowledge before and after the socialization session. The findings show a significant increase in participants' knowledge, with an average pre-test score of 63.88 rising to 68.55 in the post-test. This improvement demonstrates the effectiveness of interactive socialization in enhancing the community's understanding of food safety. The study concludes that socialization combined with pre-test and post-test evaluations effectively increases public awareness of food safety. Therefore, ongoing training and information support are recommended to strengthen the community's understanding of safe food processing and consumption practices.